Avaliação das técnicas de RT-PCR e heminested RT-PCR em cérebros de cães com sinais neurológicos compatíveis com cinomose - Cortez, Adriana; Souza, Vanessa [UNESP]; Fernandes, Telma [UNESP]; Megid, Jane [UNESP] (My University, 2015)
The diagnostic value of RT-PCR and hemi-nested RT-PCR (hnRT-PCR) was compared in brain samples of dogs presenting neurological signs compatible with canine distemper. Samples of central nervous system (CNS) were collected from 68 dogs and tested by direct immunofluorescence test (RFID) and, independent of the results, they were stored at -20°C for at least three years. They were submitted to the RT-PCR and hnRT-PCR techniques aiming to determine the gene responsible for the viral nucleoprotein decoding. Fifty-nine samples were positive for RIFD, 40 for RT-PCR (Kappa = 0.358) and 54 for hnRT-PCR (Kappa = 0.740). All nine RIFD negative samples were also negative for RT-PCR and hnRT-PCR. In spite of the storage duration and proper sample conditions, the estimated accordance between hnRT-PCR and RIFD demonstrated that hnRT-PCR technique can be applied in retrospective studies.
Evaluation of RT-PCR and hemi-nested RT-PCR in brain samples from dogs with neurologic signs compatible with distemper
Keywords: Canine distemper; Direct immunofluorescence; HnRT-PCR; Kappa index